Calcium Amido Complexes Coordinated by Tridentate Amidinate Ligands: Synthesis, Structures and Catalytic Activity in Olefin Hydrophosphination and Polymerization of Cyclic Esters. Issue 39 (5th August 2019) - Tolpygin, Aleksei O.; Cherkasov, Anton V.; Fukin, Georgy K.; Kovylina, Tatyana A.; Lyssenko, Konstantin A.; Trifonov, Alexander A.
Abstract : The reactions of [(Me3 Si)2 N]2 Ca(thf)2 with amidines 2‐(Ph2 P=NPh)C6 H4 NHC( t Bu)=N(2, 6‐R2 C6 H3 ) R = i Pr (L 1 H ); R = Me (L 2 H ) afford heteroleptic calcium amido complexes [2‐(Ph2 P=NPh)C6 H4 NC( t Bu)=N(2, 6‐R2 C6 H3 )]Ca[N(SiMe3 )2 ](thf) R = i Pr (1 ); R = Me (2 ) featuring tridentate coordination of the amidinate ligands. Complexes 1 and 2 proved to be efficient catalysts for intermolecular hydrophosphination of styrene, α‐methylstyrene, divinylbenzene and phenylacetylene with Ph2 PH and PhPH2 . Compounds 1 and 2 exhibit high catalytic activity in the ring‐opening polymerization of ε‐caprolactone and enable quantitative conversion of 500 equiv. of monomer in 5 seconds (22 °C). Polymerization of rac ‐lactide initiated by 1 and 2 proceeds much slower: 52–72 % conversion ([M]0 /[Ca]0 = 100) was reached in 12 h (20 °C). The obtained polymers are characterized by narrow polydispersities ( M w /Mn = 1.22–1.28). Catalytic activity of complexes 1 and 2 in rac ‐lactide polymerization increases significantly in the presence of 1–3 equiv. of i PrOH. Nearly quantitative (86–98 %) conversion of 100 equiv. of monomer was reached in 1 h and the obtained polymer samples were characterized by relatively narrow polydispersity (Mw /Mn = 1.51–1.68). Abstract : Heteroleptic calcium amidoamidinate complexes [2‐(Ph2 P=NPh)C6 H4 NC( t Bu)=N(2, 6‐R2 C6 H3 )]Ca[N(SiMe3 )2 ](thf) R = i Pr (1 ); R = Me (2 ) catalyze intermolecular hydrophosphination C=C and C≡C bonds and ROP of ε‐caprolactone and rac ‐lactide.